Congress and Cuba : the Helms-Burton Act. - LOWENFELD, Andreas F. (1996)
Emphasises the limits placed by Congress on the conduct of foreign affairs in using trade controls for political ends. Concludes that the legislation hampers the discretion of the executive branch: it places too much emphasis on property issues almost two generations old; it perverts US immigration and travel laws; and it seeks to impose American policy judgements on nationals of friendly foreign states in a manner that is both unlawful and unwise.